An optimized method for (15)N R(1) relaxation rate measurements in non-deuterated proteins - Gairí, Margarida (J Biomol NMR, 2015)
(15)N longitudinal relaxation rates are extensively used for the characterization of protein dynamics; however, their accurate measurement is hindered by systematic errors. (15)N CSA/(1)H–(15)N dipolar cross-correlated relaxation (CC) and amide proton exchange saturation transfer from water protons are the two main sources of systematic errors in the determination of (15)N R(1) rates through (1)H–(15)N HSQC-based experiments. CC is usually suppressed through a train of 180° proton pulses applied during the variable (15)N relaxation period (T), which can perturb water magnetization. Thus CC cancellation is required in such a way as to minimize water saturation effects. Here we examined the level of water saturation during the T period caused by various types of inversion proton pulses to suppress CC: (I) amide-selective IBURP-2; (II) cosine-modulated IBURP-2; (III) Watergate-like blocks; and (IV) non-selective hard. We additionally demonstrate the effect of uncontrolled saturation of aliphatic protons on (15)N R(1) rates. In this paper we present an optimized pulse sequence that takes into account the crucial effect of controlling also the saturation of the aliphatic protons during (15)N R(1) measurements in non-deuterated proteins. We show that using cosine-modulated IBURP-2 pulses spaced 40 ms to cancel CC in this optimized pulse program is the method of choice to minimize systematic errors coming from water and aliphatic protons saturation effects. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10858-015-9937-4) contains supplementary material, which is available to authorized users.